(untitled) (Journal of Organizational Psychology, 2025)
This study examines the workplace experiences of neurodivergent individuals in a conservation organization using the biopsychosocial model. Fifteen neurodivergent participants (13 staff and 2 postgraduates), including seven who additionally identified as disabled, shared insights in interviews designed with input from an advisory group. Facilitators of inclusion included empathy, acceptance, and use of strengths. Barriers involved sensory-overwhelming environments, limited mental health support, and cultures prioritizing overwork. Key recommendations for neuro-inclusion are fostering job fit, emphasizing well-being, and promoting flexibility and autonomy. Achieving inclusion necessitates adapting workplace practices to accommodate diverse needs, engaging neurodivergent workers in decision-making, and educating colleagues about neurodiversity.